The Role of Digital Technology in Responding to COVID-19 Pandemic: Saudi Arabia’s Experience - Khan A; Alahmari A; Almuzaini Y; Alturki N; Aburas A; Alamri FA; Albagami M; Alzaid M; Alharbi T; Alomar R; Abu Tayli M; Assiri AM; et al. (Dove Medical Press, 2021)
Anas Khan, 1, 2 Ahmed Alahmari, 2 Yasir Almuzaini, 2 Nada Alturki, 2 Alhanouf Aburas, 3 Fahad A Alamri, 2 Mohammed Albagami, 4 Mashael Alzaid, 4 Turki Alharbi, 4 Rahaf Alomar, 4 Muath Abu Tayli, 4 Abdullah M Assiri, 5 Hani A Jokhdar 6 1Department of Emergency Medicine, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2Global Center of Mass Gatherings Medicine, Ministry of Health, Riyadh, Saudi Arabia; 3Health Sciences Department, College of Health and Rehabilitation Sciences, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 4Saudi Data and Artificial Intelligence Authority, Riyadh, Saudi Arabia; 5Ministry of Health, Riyadh, Saudi Arabia; 6Deputyship of Public Health, Ministry of Health, Riyadh, Saudi ArabiaCorrespondence: Alhanouf AburasHealth Sciences Department, College of Health and Rehabilitation Sciences, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi ArabiaEmail Alhanoufaburas@gmail.comIntroduction: The novel coronavirus (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a single-chain ribonucleic acid (RNA) virus. As of March 25, 2021, the total number of positive cases and fatalities in the Kingdom of Saudi Arabia (KSA) had reached 386,300 and 6624, respectively, with a case fatality rate of 1.71%. The KSA was among the leading nations to heed the advice of WHO officials and put strict precautionary and preventive measures in place to curb the early spread of COVID-19 before it was declared a global pandemic.Methodology: This was an uncontrolled before–after study following a mixed-method approach for data collection. National and regional data were extracted from the Health Electronic Surveillance Network (HESN), a centralized public health collection system for quantitative and statistical data. Quantitative and qualitative methods have been utilized in studying data derived from tech media.Results: The Saudi authorities utilized different technological tools to aid in managing and combating the COVID-19 pandemic. In the case of Al Madinah Al Mounawarah, after the implementation of several technologies, the most important being Tawakkalna, the number of active daily cases decreased by 61%.Conclusion: The use of the Tawakkalna application was proven to be a successful method in fighting the COVID-19 pandemic in the KSA. This vital and essential experience warrants the use of different digital technology that offers a personalized profile displaying the person’s status (affected, vaccinated, or no history of infection). This application played and will continue to play a crucial and effective role in pandemic containment in Saudi Arabia.Keywords: digital technology, risk management, Saudi Arabia, applications